Integrated urban-rural development and common prosperity: Connotation, international experience and implementation path [in Chinese] - Chen, Kevin Z.; Mao, Rui; Zhang, Yunfei (Zhejiang University, 2022)
Since the 18th National Congress of the Communist Party of China, China’s economicdevelopment has entered a new stage. Under the circumstances, the goal of “Common Prosperity” has attracted more and more attention over the past several years. China’s long-term implementation of urban-biased policies led to a huge gap between urban and rural areas for a long time and hindered the realization of common prosperity. The report of the 19th National Congress of the Communist Party of China put forward a new concept of “Integrated Urban-Rural Development” to solve the problem of unbalanced development between urban and rural areas. This study points out that integrated urban-rural development is an important path to achieve the goal of common prosperity due to the huge gap between urban and rural areas. Besides, narrowing the gap between urban and rural areas in various dimensions is also the main direction of common prosperity. Firstly, the study illustrates that through integrated urban-rural development, it is possible to (1) reduce the income gap between urban and rural areas to promote the realization of common prosperity in the material dimension; (2) facilitate the equal supply of basic public services between urban and rural areas to promote the realization of common prosperity in the dimension of rights; (3) balance urban and rural development capabilities to promote the realization of common prosperity in the dimension of development opportunities; (4) coordinate the construction of urban-rural spiritual civilization to promote the realization of common prosperity in the spiritual dimension; (5) stimulate the integration between urban and rural ecological environment to promote the realization of common prosperity in the ecological dimension. In addition, after sorting out the international experience of integrated urban-rural development, the study finds that major developed countries and some emerging countries have established (1) an urban-rural economic linkage mechanism of in-depth integration and benefit sharing; (2) an urban-rural ecological environment linkage mechanism of overall planning and sustainable development; (3) an urban-rural public service linkage mechanism of urban-rural equivalent and comprehensive coverage. Aiming at the goals of common prosperity concerning farmers’ rights, industrial development, education equity and ecological value conversion, the paper combines the opinions of the experts participating in the “Integrated Urban-Rural Development and Common Prosperity” academic seminar with literature to propose seven policy paths for integrated urban-rural development: (1) promoting urban-rural economic integration by achieving equal rights to urban and rural development; (2) taking advantage of industrial clusters development model to promote urban-rural economic integration; (3) improving the income distribution system to promote urban-rural economic integration; (4) promoting the ecological integration between urban and rural areas with the realization of ecological products value; (5) facilitating the integration of urban and rural public services with the cultivation of early childhood human capital; (6) stimulating the integration of urban and rural public services with the realization of education equity; (7) advancing the integration of urban and rural public services with the development model of “inter-village integration”. The paper reveals that urban-rural integration requires further institutional reform, as well as the different varieties of policies aiming at special demands. Therefore, grassroots innovation and careful consideration of the differences across different groups and different regions could be fully guaranteed to achieve common prosperity.